Improving a circular reverse logistics to handle product return: Insights from a global electronics services provider - Nur Atiqah Batrisyia, .; Fernando, Yudi (Penerbit Universiti Malaysia Pahang, 2024)
In the retail industry, consumers often return goods for various reasons, including damage, flaws, or plain dissatisfaction. The storing of returned goods can result in insufficient arrangement of the existing storage space and capacity. Such issue can cause problems like longer processing times, higher operating costs, and reduced customer satisfaction, hence necessitating prompt response. Therefore, this case study was conducted in a global electronics services provider to examine how circular reverse logistics can enhance the handling of product returns as well as developing a smart product return strategy. It is believed that creating a plan for product returns and integrating internal process improvements with external collaboration are highly important. The results showed that the organisation can establish a circular reverse logistic process to lower the cost and amount of product returns, enhance consumer service, and boost profitability. Such findings can benefit organisations wishing to establish circular reverse logistics procedures to handle product returns.